2016
DOI: 10.3855/jidc.7474
|View full text |Cite
|
Sign up to set email alerts
|

Etiological profile of early neonatal bacterial sepsis by multiplex qPCR

Abstract: Introduction: Given the major impact in terms of morbidity and mortality that episodes of early neonatal sepsis (ENS) have on both newborns and health systems, this study aimed to identify the etiological profile of early neonatal bacterial sepsis by a multiplex quantitative real-time polymerase chain reaction (qPCR). Methodology: Blood samples from newborns diagnosed with clinical ENS and hospitalized in neonatal intensive care units (NICUs) were collected and analyzed using the multiplex qPCR method to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…According to Vergano et al, the infections with negative cultures are the most frequent ones, and can be confirmed in less than 1% of the cases. 25 Other studies found a positivity rate of 2.3 17 , 3.0 26 and 4.6%. 27 The optimization of the laboratory diagnosis requires fast tests, with better sensitivity and high specificity, which still do not exist.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to Vergano et al, the infections with negative cultures are the most frequent ones, and can be confirmed in less than 1% of the cases. 25 Other studies found a positivity rate of 2.3 17 , 3.0 26 and 4.6%. 27 The optimization of the laboratory diagnosis requires fast tests, with better sensitivity and high specificity, which still do not exist.…”
Section: Discussionmentioning
confidence: 94%
“…A Brazilian study that used universal primer (q-CRP) showed positivity in all patients diagnosed with clinical sepsis, and in 97% of the studied patients, the DNA of one or more among the seven analyzed bacteria was found. 26 A remark for these tests is that the positive result can represent only one contamination, and, if performed in patients without any clinical indication, it would possibly lead to excessive treatment indications.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional microbiological methods may frequently fail to identify pathogens because of technical issues or traits intrinsic to microorganisms that limit sepsis detection. Although new diagnostic approaches have been developed to replace conventional methods, implementation in developing countries will be challenging because of a lack of resources [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…EL-Amir et al 15 demonstrated a prevalence of Gram-negative bacteria among patients with EONS but they found that the most common Gram-negative bacteria causing EONS was E.coli. Also, Silva-Junior et al 34 showed that E. coli, Staphylococcus aureus, and Streptococcus agalactiae were the main causative organisms of EONS.…”
Section: Discussionmentioning
confidence: 99%